What matters when examining the performance of salespersons? Analyzing the boundary conditions of personal dispositional factor - Naeem, Muhammad; Shah, Fayaz Ali; Kakakhel, Shahid Jan; Gul, Shabana (Frontiers in Psychology, 2022)
Purpose: This study intended to examine the effect of developmental and evaluative purpose of performance appraisal on job meaningfulness. Further, the study also aimed to assess the moderating effect of personal dispositional factors i.e. internal and external locus of control between developmental and evaluative performance appraisal and job meaningfulness. Design/methodology/approach: A total of 295 questionnaires were received from salespersons working in national and multinational pharmaceutical companies in Khyber Pakhtunkhwa, Pakistan. Data were gathered using a time-lagged study design using a convenience sampling technique. Data collected via questionnaires were analyzed using PLS-SEM to assess measurement and structural model for testing hypotheses. Findings: Results revealed that developmental PA significantly influences job meaningfulness while evaluative PA failed to influence job meaningfulness. Furthermore, moderating effect of external locus of control on the relationship of developmental PA and job meaningfulness while the rest of moderating hypotheses failed to influence the relationship among developmental and evaluative PA with job meaningfulness. Practical implications: The results can be used as a building block that in order to bring positive work outcomes in the form of meaningful work. Organizations shall use their PA as a development tool instead of instrumental or evaluative for making the work more meaningful to the employees. Originality/value Extant literature is limited in terms of assessing the dimensions of performance appraisal (developmental and evaluative) in predicting workplace outcomes. Also, multidimensions of locus of control have been limited examined in the existing literature between HR practices and work outcomes. The current study has filled these gaps in contemporary literature.